Method for producing composite fiber material having particularly low degree of fiber deformation

Through the relative movement of the thermoplastic molding composition with the chemically reactive functional groups and the high temperature and high pressure consolidation of the reinforced fibers, the problems of brittle fracture and insufficient optical performance of the fiber composite material are solved, and high bending strength and low deformation are achieved and fiber composite materials with excellent surface quality.

CN119156415APending Publication Date: 2024-12-17BOND LAMINATES GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095641.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2022-11-25
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing fiber composites are prone to brittle fracture when completely failed, resulting in high-speed discrete debris, increasing the risk of accidents, and insufficient optical performance and surface smoothness.

Method used

Reinforced fibers treated with silane compounds and thermoplastic molding compositions with chemically reactive functional groups are embedded in the reinforcing fibers by relative movement and consolidated under high temperature and pressure to form an optimized fiber-matrix bonding Adhere to fix the fiber arrangement to reduce fiber deformation and air inclusion.

Benefits of technology

It improves the bending strength of the fiber composite material, reduces fiber deformation and air inclusion, enhances optical properties and surface quality, and ensures the material's stress crack resistance and processing ease.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005113226080000011
    Figure HDA0005113226080000011
  • Figure HDA0005113226080000012
    Figure HDA0005113226080000012
  • Figure HDA0005113226080000021
    Figure HDA0005113226080000021
Patent Text Reader

Abstract

The invention relates to a method for producing a fibre composite material comprising a thermoplastic moulding composition A and at least one layer of reinforcing fibres B. A thermoplastic molding composition A is integrated as a matrix into at least one layer of reinforcing fibers B, the molding composition being integrated by moving the molding composition relative to the reinforcing fibers B in a consolidation step, the reinforcing fibers B remaining stationary except for a one-dimensional production advance movement, the thermoplastic molding composition A has at least one chemically reactive functional group, and the surface of the reinforcing fibers B is treated with a coating, and the functional group concentration of the chemically reactive functional groups of the molding composition A is at least 0.3 mol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a fiber composite material, which fiber composite material comprises a thermoplastic molding composition A and at least one layer of reinforcing fibers B, wherein the thermoplastic molding composition A as a matrix is ​​embedded in the at least one layer of reinforcing fibers B, wherein the embedding occurs due to the relative movement of the molding composition relative to the reinforcing fibers B in a consolidation step, in which the reinforcing fibers B remain stationary except for a one-dimensional production feed, and the thermoplastic molding composition A has at least one chemically reactive functional group, and the surface of the reinforcing fibers B has been treated with a size, and the concentration of functional groups for the chemically reactive functional groups of the molding composition A is at least 0.3 mol%. Background Art

[0002] Fiber composites (also referred to as organic sheets in planar or two-dimensional form) have a thermoplastic polymer matrix in which one or more fiber weaves and / or one or more fiber scrims are embedded. The fibers used to produce fiber composites are usually glass fibers, aramid fibers or carbon fibers, which are introduced into the thermoplastic polymer matrix as continuous fibers or long fibers. The fiber length of the long fibers here is in the range from 1 mm to 50 mm; fibers with a length of more than 50 mm are referred to as continuous fibers. Compared to fiber composites with shorter fibers, fiber composites based on continuous fibers have the highest stiffness and strength values.

[0003] Fiber composites are usually based on a large number of reinforcing fibers embedded in a polymer matrix. Fiber composites have different areas of use. Fiber composites are preferably used in the automotive and aviation sectors. In this field of application, the reinforcing fibers are intended to prevent the polymer matrix from tearing or otherwise fragmenting, thereby reducing the risk of accidents due to component crushing. Many fiber composites are able to absorb relatively high forces under load before completely failing. At the same time, fiber composites are known for high strength and stiffness compared to conventional unreinforced materials, while having a low density and other favorable properties, in particular good aging and corrosion resistance.

[0004] Another advantage of fiber composites is that the strength and stiffness of fiber composites can adapt to the direction and type of load. In this context, reinforcing fibers are mainly responsible for the strength and stiffness of fiber composites. In addition, the arrangement of fibers in fiber composites determines its mechanical properties. In contrast, the matrix is ​​usually mainly used to introduce force to be absorbed into a single reinforcing fiber, and the spatial arrangement of the reinforcing fibers is maintained in the desired direction. In order to ensure the best transmission of force, the reinforcing fibers should be as straight as possible, i.e., there is no deformation in the polymer matrix. Since both reinforcing fibers and matrix materials are variable, a variety of possible combinations of reinforcing fibers and matrix materials can be used by those skilled in the art when producing fiber composites.

[0005] One technical challenge is that in the event of a complete failure, fiber composites may experience brittle fracture, meaning that a complete failure may generate fragments that can leave the fracture site at high speeds. As a result, fiber composite-based products may be subject to high or sudden stresses if they break or shatter, creating a considerable risk of accidents.

[0006] Therefore, it is desirable to provide fiber composite materials with a wide stress range, in which complete failure is unlikely. In addition, there is a need for good optical properties, as well as the possibility of using fiber composite materials to produce various components with smooth surfaces.

[0007] EP 1 923 420 B1 describes a fiber composite material with a matrix consisting of thermoplastics, in which a reinforcing fiber layer is embedded. A first group of reinforcing fibers is joined to the matrix by a first fiber-matrix adhesion. A second group of reinforcing fibers is also joined to the matrix by a second fiber-matrix adhesion. The second fiber-matrix adhesion is lower than the first fiber-matrix adhesion. In the case of complete failure, different fiber-matrix adhesions achieve improved fracture characteristics. The matrix material proposed in EP 1 923 420 B1 is a thermosetting material (such as polyester) and thermoplastics polyamide and polypropylene.

[0008] Thus, EP 1 923 420 B1 focuses on the bonding of reinforcing fibers and polymer matrix, referred to as fiber-matrix adhesion, in the production of fiber composite materials.

[0009] In order to optimize fiber-matrix adhesion and in order to compensate for " low chemical similarity " between the fortifying fiber surface and the surrounding polymer matrix, fortifying fiber is regularly pre-treated.It has been found that so-called sizing material can be used for this purpose, and preferably in these sizing materials, add so-called adhesion promoter.Even in the fiber production process, also sizing material or sizing material / adhesion promoter will be regularly applied to fortifying fiber, to improve its further processability, particularly by weaving, laying or stitching.If this sizing material does not need to be used for the further processing of fortifying fiber later, then it must first be removed in extra method step, preferably by burning.

[0010] But, except sizing material, it may also be favourable to apply adhesion promoter on the fortifying fiber processed in the extra method step.Sizing material and / or adhesion promoter form a layer on the fortifying fiber surface, which can significantly determine the interaction of fortifying fiber and environment.Nowadays, there are many different sizing materials and adhesion promoters available for use.According to the fortifying fiber of use field, the matrix of use and the use, those skilled in the art can select suitable sizing material and suitable adhesion promoter compatible with matrix and fortifying fiber.

[0011] WO 2016 / 170131 A1 teaches the use of a fiber composite material W having a sandwich structure, the sandwich structure being formed by A) a thermoplastic plastic layer w and B) another thermoplastic plastic layer T and / or a foam layer S, the thermoplastic plastic layer w containing a) a thermoplastic molding composition A as a matrix, b) a layer of reinforcing fibers B, and c) optional additives c as components, wherein the reinforcing fiber layer B is embedded in the matrix of the thermoplastic molding composition A, and in the production of the material layer w, the thermoplastic molding composition A has at least one chemically reactive functional group, which in turn reacts with chemical groups on the surface of the reinforcing fibers B; wherein the another layer T and / or S is permanently bonded to the material layer w, thereby improving the mechanical stability of the shaped product produced thereby.

[0012] DE 10 2016 102081 A1 relates to a method for producing a fiber-reinforced component, comprising the steps of laying fibers (16) into a casting mold (10) having a movable insert (12), pouring a matrix material (22) into the casting mold (10), and moving the insert (12) in a direction of movement (B) while injecting the matrix material (22). DE 10 2016 102081 A1 envisages that, before injecting the matrix material (22), the fibers (16) are introduced in a direction transverse to the direction of movement (B) relative to the insert (12).

[0013] EP 3 286 258 B1 describes a method for producing a fiber composite material comprising a thermoplastic molding composition A and at least one layer of reinforcing fibers B, wherein at least one layer of reinforcing fibers B is embedded in a matrix comprising the thermoplastic molding composition A, and wherein the thermoplastic molding composition A has at least one chemically reactive functional group, the surface of the reinforcing fibers B is treated with a silane sizing agent, and the concentration of the functional groups of the chemically reactive functional groups is at least 0.3 mol%. EP 3 286 258 B1 does not take into account the fiber deformation that occurs in the production of the fiber composite material. The method described in EP 3 286 258 B1 does not prevent this.

[0014] WO 2016 170104A1 relates to the use of a thermoplastic fiber composite material, which comprises a) at least one thermoplastic molding composition A as a matrix, b) at least one layer of reinforcing fibers B) and c) optionally at least one additive c, wherein the at least one layer of reinforcing fibers B is embedded in the matrix of the thermoplastic molding composition and the thermoplastic molding composition A has at least one chemically reactive functional group, which reacts with chemical groups on the surface of the component B material during the production of the fiber composite, for the production of large household appliances (white goods) such as domestic appliances, which makes the product lighter.

[0015] In the prior art, reinforcing fibers, in particular glass fibers, are often treated with sizing to protect the reinforcing fibers from mutual damage in the case of mutual friction. For example, DE-A 2160778 discloses glass fiber reinforced styrene polymers based on reinforcing fibers treated with sizing. It is said that mutual damage caused by wear can be prevented, and in the case of mutual mechanical interaction, cross crushing (fracture) is said not to occur.

[0016] The size can also facilitate the cutting operation of the reinforcing fibers to obtain equal stacking lengths. In addition, the size can prevent the reinforcing fibers from agglomerating. The dispersibility of the short fibers in water can be improved by the size, which makes it possible to obtain a uniform fabric by wet laying.

[0017] The size also helps to establish improved integrity between the glass fibers and the polymer matrix, where the glass fibers act as reinforcement fibers. This principle is particularly applicable in the case of glass fiber reinforced plastics (GFRP).

[0018] Besides the adhesion promoters already mentioned, the sizes for glass fibers preferably contain a large number of further components, more preferably film formers, lubricants or wetting agents.

[0019] Film formers protect the glass fibers or glass filaments from mutual friction and can additionally increase affinity for synthetic resins, thereby increasing the strength and integrity of fiber composites based on glass fibers. Preferred film formers are starch derivatives, polymers and copolymers of vinyl acetate and acrylates, epoxy resin emulsions, polyurethane resins and polyamides. Film formers are preferably used in a proportion of 0.5 to 12% by weight, based on the total size.

[0020] Lubricants impart softness to glass fibers and glass fiber-based products, in particular braids, and reduce mutual friction between glass fibers. However, the adhesion between glass fibers and synthetic resins is generally impaired by the use of lubricants. The lubricants used are preferably greases, oils or polyalkyleneamines. The amount of these lubricants used is preferably in the range of 0.01 to 1% by weight, based on the total size.

[0021] Wetting agents lead to a reduction in surface tension and improve the wettability of the glass fibers or glass filaments with the size. For aqueous sizes, polyfatty acid amides should preferably be used as wetting agents in an amount of 0.1 to 1.5% by weight, based on the total size.

[0022] Preferably use organofunctional silane as adhesion promoter to improve the adhesion of polymer on the reinforcing fiber surface.Particularly preferably, the organofunctional silane used as adhesion promoter is aminopropyl triethoxysilane, methacryloxypropyl trimethoxysilane or glycidyloxypropyl trimethoxysilane.Here, these silanes that add in the water-based size are usually hydrolyzed to silanols.Then, these silanols can react with the reactive reinforcing fiber surface, thereby form an adhesive layer, and a preferred thickness is about 3nm.

[0023] In the case of using glass fibers as reinforcing fibers, low molecular weight functional agents in the matrix polymer can react with silanol groups on the surface of the glass fibers, and then these low molecular weight agents further react (especially in epoxy resins), which can ensure chemical bonding of the glass fibers to the polymer matrix. However, such a process is time-consuming and takes about 30 minutes to more than an hour before the polymer is completely cured (especially the above-mentioned epoxy resins).

[0024] It is also known to functionalize silane sizings by reaction with polymers. Through functionalization of low molecular weight polycarbonate types, glass fiber braids or glass fiber scrims can be effectively impregnated with polycarbonate and "grafting" is achieved by reaction of functional groups in the polycarbonate with the glass fiber surface. However, this method has the disadvantage that it is generally not suitable for polycarbonate (PC). Only low molecular weight (i.e. low viscosity) polycarbonates can be used in this way, which in turn have extremely poor applicability and low resistance to agents that trigger stress cracking (especially polar solvents). Summary of the invention

[0025] Starting from the prior art, the object of the present invention is therefore to provide a method for producing a fiber composite material based on a reinforcing fiber fabric, as a result of which, based on the same matrix polymer, the fiber composite material and the shaped bodies produced therefrom have improved properties, in particular with regard to their flexural strength, compared to the above-mentioned prior art.

[0026] The fiber composite materials produced according to the invention and the shaped bodies produced therefrom are based on a strong composite (which can be quantified by its flexural strength) of a reinforcing fiber weave and a matrix polymer, which is easy to process, is essentially inert to conventional solvents, has good resistance to stress cracking, and has minimal fiber deformation.

[0027] In the context of the present invention, fiber deformation refers to any deviation from the ideal braid form as defined in DIN ISO 9354. In an ideal braid used as fabric F according to the invention, the fibers are ideally parallel and stretched, usually continuous fibers are used. In the context of the present invention, low fiber deformation or no deformation means that the deviation of the fiber center line relative to the filament length in the two-dimensional projection of the glass fiber braid in the plane of the braid is not more than 15%.

[0028] According to the present invention, the glass fiber fabric used as fabric F cannot be produced in an ideal form by physical and technical means. They are the result of continuous fiber weaving, in particular the weaving of rovings. The weaving of glass fibers is inevitably associated with the fluctuation of the fibers. Fluctuation has a special effect of reducing the compressive strength parallel to the fibers. A characteristic of fluctuation is that the fibers move up and down alternately relative to the plane of the fabric F, and are therefore not in an ideal parallel and stretched form. Considering the two-dimensional projection of the wavy fabric, the fibers are in an ideal stretched form in the warp and weft directions of the fabric. Ideal parallelism is essential for the optimal transmission of forces in the fibers. If a thermoplastic polymer matrix is ​​embedded in the fabric F according to the present invention, the ideal parallelism of the fibers can be maintained. Deviations from the ideal parallelism are called fiber deformation and are measured by visual monitoring according to DIN EN ISO 13015, for example by means of a suitable instrument or a camera-based system. The position of the fiber centerline is determined in the main direction relative to the length of the filament. A filament defines a bundle of fibers, which is also called roving, yarn, fiber bundle or filament bundle.

[0029] The present invention provides a method for producing a fiber composite material, the fiber composite material comprising a thermoplastic molding composition A (as a polymer matrix M) and reinforcing fibers B, the method comprising the following steps:

[0030] i) providing at least one fabric F in the form of a woven fabric consisting of reinforcing fibers B treated with a silane size,

[0031] ii) providing a thermoplastic molding composition A serving as matrix M, which, based on component A, has at least 0.3 mol % of chemically reactive functional groups in the form of functional monomers,

[0032] iii) optionally incorporating at least one additive C into the thermoplastic molding composition A,

[0033] iv) introducing the thermoplastic molding composition A serving as matrix M into at least one fabric F by embedding the thermoplastic molding composition A in the reinforcing fibers B by means of a relative movement in which the reinforcing fibers B remain stationary except for a continuous or discontinuous one-dimensional production feed, and consolidating the composite material consisting of the at least one fabric F and the matrix M,

[0034] v) reacting the chemically reactive functional groups of the thermoplastic molding composition A with the polar groups at the surface of the reinforcing fibers B which have been treated with the silane size,

[0035] vi) cooling the fiber composite material, and optionally further method steps,

[0036] wherein the chemically reactive functional groups of the thermoplastic molding composition A are based on components selected from the group consisting of maleic anhydride, N-phenylmaleimide and glycidyl (meth)acrylate, and steps iv) to vi) are carried out at a temperature of at least 150° C. and steps v) to vi) are carried out by pressing under elevated pressure.

[0037] The method according to the invention surprisingly provides a particularly deformation-free fiber composite material.

[0038] A feature of the method of the present invention is that a matrix M is introduced into at least one fabric F. The matrix M flows into the gaps of the reinforcing fibers B treated with silane sizing here. Here, the excess sizing is displaced from the rovings, yarns, fiber bundles or tows of the reinforcing fibers B. The fiber composite material produced according to the present invention is characterized in that all individual fibers are completely coated by the matrix M. This not only produces optimized fiber-matrix adhesion, but also improves the fixation of the reinforcing fibers in their spatial arrangement, and therefore, compared with the fiber composite material produced according to the above-mentioned prior art, the fiber composite material produced according to the present invention has lower deformation.

[0039] In method step iv), the matrix M is introduced into at least one fabric F, preferably by melting the thermoplastic molding composition A and contacting it with at least one fabric F composed of reinforcing fibers B, as provided in method step i).

[0040] The melting of the thermoplastic molding composition A and the contacting of the melt with the reinforcing fibers B can be carried out in any manner suitable for the purpose. In this impregnation, the matrix M based on the thermoplastic molding composition A is converted into a free-flowing state and the reinforcing fibers B are wetted to form an interface layer.

[0041] Method steps iii), iv), v) and vi) can also be carried out simultaneously. According to the present invention, at least one thermoplastic molding composition A contains chemically reactive functional groups in the form of functional monomers based on at least 0.3mol% of component A. Preferably, at least one thermoplastic molding composition A comprises at least one copolymer A-1, which comprises monomers AI that form covalent bonds with the polarity or functional group BI of reinforcing fiber B. When method steps iv), v) and vi) are carried out simultaneously, after at least one thermoplastic molding composition A contacts reinforcing fiber B, chemical reaction occurs immediately, wherein monomers AI and the surface of reinforcing fiber B form covalent bonds (usually through the key with functional group BI). This is preferably esterification, particularly the esterification of maleic anhydride monomers with the silanol groups in the reinforcing fiber. Alternatively, the formation of covalent bonds can also be initiated in a separate step, particularly by raising the temperature, by means of free radical initiators or by light initiation or a combination of these methods. This can be achieved at any suitable temperature.

[0042] Steps iv) to vi) are carried out at a temperature of at least 150° C., preferably at least 175° C., more preferably at least 200° C., particularly preferably in the range of 230° C. to 300° C. It should preferably be ensured that as little thermal decomposition as possible occurs and that the reactants used and the components used do not thermally decompose.

[0043] In a preferred embodiment, when carrying out steps iv) to vi), the residence time at a temperature of ≥ 200° C. is not more than 10 minutes, preferably not more than 5 minutes, more preferably not more than 2 minutes, particularly preferably not more than 1 minute. Typically, 1 to 60 seconds are sufficient for process steps iv) to vi) and the heat treatment that takes place therein.

[0044] The process, in particular steps iv) to vi), can in principle be carried out at any pressure. Method steps v) and vi) are preferably carried out at elevated pressure, which can improve the properties of the produced fiber composite material. In particular, surprisingly, the appearance of the surface can be improved in this way. Experiments in the context of the present invention have shown that, in particular when method step vi) is not carried out at elevated pressure, the surface roughness and the proportion of air inclusions in the fiber composite material increase.

[0045] Therefore, in a preferred embodiment, process steps iv) to vi) are carried out at a pressure in the range of 5 to 100 bar and a pressing time in the range of 1 to 60 seconds, more preferably at a pressure in the range of 10 to 30 bar and a pressing time in the range of 2 to 40 seconds.

[0046] Preference is given to using a polypropylene (AI) provided with at least one chemically reactive functional group as the thermoplastic molding composition A in the matrix M. The use of amorphous thermoplastics, in particular styrene copolymers or polycarbonates, can significantly improve the surface quality of the produced fiber composites compared to semi-crystalline thermoplastics, since the lower shrinkage of amorphous thermoplastics improves the surface topology (due to fiber-rich areas (crossover points in the fabric) and fiber-poor areas). Comparable surface qualities can surprisingly also be achieved with semi-crystalline thermoplastics if method step vi) is carried out under elevated pressure according to the invention.

[0047] In method step v), in particular in method step vi) consolidation process, the relative movement of thermoplastic molding composition A relative to reinforcing fibers B displaces the air present between reinforcing fibers, which reduces the air inclusions in the fiber composite material and the composition of manufacture, and sets up good bonding between thermoplastic molding composition A and reinforcing fibers B. A preferred object of the present invention is to obtain (mostly) non-porous material composites after impregnation and consolidation. In the context of the present invention, "non-porous" means that the fiber composite material contains less than 5% air or vacuole by volume, which can be detected by optical test methods, x-ray imaging, density measurement or ashing, particularly according to ASTM D2734-09.

[0048] Alternatively, these method steps can be performed in a separate order.For example, therefore the layer of forcing fiber B can be prepared with the forcing fiber B of different preparations, wherein the matrix M impregnated forcing fiber B with thermoplastic molding composition A is carried out.After this, there can be an impregnation layer of the forcing fiber B with different fiber-matrix adhesions, which can be consolidated in a further step, and obtains the material complex as fiber composite material.Before the layer of forcing fiber B and the matrix M lamination of thermoplastic molding composition A, at least some forcing fibers B can be pre-treated, and in this process, later stage fiber-matrix adhesion can be affected.Pre-treatment can preferably comprise coating step, etching step, heat treatment step or mechanical surface treatment step.But, especially, also can partially remove the adhesion promoter applied by heating a part of forcing fiber B.

[0049] During the production process of the invention, the reinforcing fiber layers can be completely bonded to each other, which is called lamination. Such a fiber composite mat provides improved strength and stiffness in the direction of the reinforcing fibers and can be further processed particularly advantageously.

[0050] Particularly preferred embodiments and reactants of the process

[0051] Method step i)

[0052] The at least one fabric F provided in method step i) is preferably based on a fabric consisting of continuous fibers, including fibers which are the product of twisting together individual fibers. According to "http: / / de.wikipedia.org / wiki / Faser-Kunststoff-Verbund", in the case of reinforcing fibers, in particular glass fibers, short-cut fibers (also called short fibers) with a length in the range of 0.1 to 1 mm are distinguished from long fibers with a length in the range of 1 to 50 mm and continuous fibers with a length L>50 mm.

[0053] Therefore, according to the present invention, the reinforcing fibers F that have been processed into a fabric are preferably not short fibers ("chopped fibers"); therefore, the fiber composite material produced according to the present invention is preferably not a short fiber reinforced fiber composite material. Preferably, according to the present invention, at least 50% of the reinforcing fibers B have a length of at least 5 mm, more preferably at least 10 mm or greater than 100 mm, wherein the length of the reinforcing fibers B also depends on the size of the shaped product T produced from the fiber composite material F.

[0054] According to the invention, the fabric used in method step i) is preferably based on continuous fibers, which are in the form of rovings, yarns, fiber bundles or filament bundles before processing to produce the fabric. Therefore, it is particularly preferred to use roving fabrics, yarn fabrics or silk fabrics.

[0055] This fabric is preferably used as fabric F in method step i). In a preferred embodiment, the invention therefore also provides a method for producing a fiber composite material which has a layer structure in the fabric F and at least two layers of fabric.

[0056] The layers can preferably be constructed identically or differently. Therefore, in a preferred embodiment, the invention relates to a method for producing a fiber composite material having a layered structure and containing more than two, preferably more than three woven layers. Preferably, all layers can be constructed identically or some layers can be constructed differently, where "different" refers to the type of weaving, the weaving pattern and the weaving material. The way in which the warp and weft threads alternate, and the distance they extend under or over each other, determines the pattern of the woven fabric.

[0057] The fiber composite material produced by the method of the present invention is penetrated by at least one fabric F, preferably by a large part. Here, "large part penetration" means that at least one fabric F penetrates more than 50%, preferably at least 70%, in particular at least 90% of the length of the fiber composite material produced according to the present invention. Here, the length of the fiber composite material is the maximum extent in any of the three spatial directions. More preferably, at least one fabric F penetrates more than 50%, even more preferably at least 70%, particularly preferably at least 90% of the area of ​​the fiber composite material produced by the method of the present invention. Here, the area is the area in two of the three spatial directions to the maximum extent.

[0058] The method of the invention preferably produces a flat or two-dimensional fiber composite material. In the case of a flat or two-dimensional fiber composite material preferred according to the invention, the fiber center lines of the fabric F or the individual filaments of the continuous fibers for the fabric extend along the length of the two-dimensional fiber composite material within a window with a height of ≤15%, preferably not more than ≤10%, in particular not more than ≤5%.

[0059] The flatness of the fiber composite material produced according to the invention is determined by its thickness. A fiber composite material is flat for the purposes of the present invention when the thickness of a 300 mm x 300 mm sheet of the fiber composite material does not differ from the average sheet thickness by more than 10% at any point, wherein the sheet thickness is measured at at least 4 points more than 100 mm apart from each other using a thickness gauge with a flatness measuring head. In the case of smaller board sizes, the fiber composite material is considered flat for the purposes of the present invention when the mentioned limits are scaled using the ratio of the smaller board size to the 300 mm x 300 mm board size and measured by the same test method.

[0060] Preferably, the at least one fabric F provided in method step i) is based on at least one fabric consisting of reinforcing fibers B treated with a silane size. More preferably, the reinforcing fibers B used are glass fibers having silane groups as chemically reactive functional groups on the surface.

[0061] The invention most preferably provides in method step i) at least one fabric F which is based on at least one fabric consisting of glass fibers having silanol groups as chemically reactive functional groups on the surface.

[0062] Preferably, 5 to 80 parts by mass, more preferably 10 to 75 parts by mass, even more preferably 20 to 70 parts by mass, and particularly 25 to 68 parts by mass of reinforcing fiber B is used based on 100 parts by mass of the fiber composite material produced by the method of the present invention.

[0063] The reinforcing fibers B are used in the form of a fabric F. The reinforcing fibers B may be any fibers having a surface containing functional groups BI which can form covalent bonds with monomers AI of component A.

[0064] It is well known that the physicochemical properties of fiber composites based on reinforcing fibers, especially fiber composites based on glass fibers, and resins are influenced by the affinity, adhesion and therefore shear strength at the phase boundary between the reinforcing fibers or glass fibers and the polymer matrix. The role of the size is to establish a compatible bond between the reinforcing fibers (especially glass fibers) and the surrounding resin and to ensure the producibility and processability of the roving or preliminary yarn.

[0065] Reinforcing fibers, especially glass fibers, are sensitive to indentation and scour, regardless of their chemical composition. Therefore, even during the fiber drawing process, it is necessary to take precautions by applying a sizing compound to protect the reinforcing fibers, especially glass fibers, from the effect of glass-to-glass scour, thereby protecting them from the risk of mechanical damage.

[0066] The composition of the size influences not only the integrity, hardness, stiffness or surface properties of products based on reinforcing fibers or glass fibers (especially woven fabrics), but also the processing steps, such as the fiber drawing process (fiber tension), winding (package construction) and drying process (drying temperature, drying time), and in particular the further processability.

[0067] The size used for reinforcing fibers, especially glass fibers, is mainly composed of one or more film formers, lubricants, wetting agents and one or more adhesion promoters (coupling agents). The film former imparts the required integrity to the entire filament (especially roving), protects the glass filaments from mutual friction, and helps to enhance the affinity for synthetic resins, thereby improving the strength of the fiber composite material manufactured according to the present invention. Since the film former layer is dissolved in the matrix through possible chemical reactions with the polymer matrix, the adhesion and shear strength at the phase boundary of the reinforcing fibers or glass fibers and the synthetic resin can be improved, thereby improving the strength and toughness of the composite material.

[0068] The film former used is preferably a starch derivative, a polymer and copolymer of vinyl acetate and acrylate, an epoxy resin emulsion, an epoxy polyester resin (see: EP-A-0 027 942), a polyurethane resin, a polyolefin resin, or a mixed emulsion of polyvinyl acetate and polystyrene, and its amount is in the range of 0.1 to 12.0 parts by mass based on 100 parts by mass of the total rubber.

[0069] The lubricant in the size imparts the necessary softness to the product, in particular the textile glass roving to be treated therewith, and reduces the mutual friction of the reinforcing fibers, preferably glass fibers, during its production and during further processing, in particular by weaving. However, many lubricants also have the same adhesion to the reinforcing fibers, in particular glass fibers, and the resin. The lubricant used is in particular a grease, oil, wax or polyalkyleneamine in an amount ranging from 0.01 to 1.0 parts by mass, based on 100 parts by mass of the total size.

[0070] The wetting agent as a component of the size reduces the surface tension of water and improves the wettability of the reinforcing fibers (preferably glass fibers) with the size. The wetting agent used in the aqueous size, preferably in the form of an emulsion, is in particular a poly(fatty acid amide), the amount of which is in the range of 0.1 to 1.5 parts by mass based on 100 parts by mass of the total size.

[0071] Most polymers used as matrix have only low affinity (if any) for glass, so according to the present invention, glass fibers are preferably used as reinforcing fibers. Adhesion promoters establish a bridge between glass fibers and polymers, which enables the complete transmission of forces in fiber composite materials or composites. Adhesion promoters increase the adhesion of polymers to glass surfaces. According to the present invention, the adhesion promoters preferably used are organofunctional silanes, in particular γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane. In the case of glass fibers, the amount of these adhesion promoters in the sizing material is preferably in the range of 0 to 1.0 parts by mass based on 100 parts by mass of the total sizing material.

[0072] Before the silanes used as adhesion promoters are added to the aqueous size, they are preferably hydrolyzed to silanols. Such hydrolyzate solutions have only limited stability and tend to condense. The layer containing the adhesion promoter, called polymer size, may also contain other additives, preferably primers, antistatic agents or emulsifiers, which are intended to achieve specific effects.

[0073] The auxiliary components used in rubber compounds are common knowledge and, for example, in KL - The Manufacturing Technology of Continuous Glass Fibers, described in Elsevier Scientific Publishing Corp. Amsterdam-Oxford-New York, 1983.

[0074] According to the present invention, the surface of the fortifying fiber B used, particularly glass fibre, has been processed with silane sizing. This sizing is used as a lubricant in the weaving of fortifying fiber B or glass fibre in particular, and can optionally be removed by chemical means after weaving. The fortifying fiber B used is more preferably the glass fibre with the hydroxyl of silanol group form as chemically reactive functional group B1 on its surface.

[0075] In one embodiment, the surface of the reinforcing fiber B or the glass fiber may have other functional groups B-II, in particular, hydroxyl groups, ester groups or amino groups.

[0076] The reinforcing fibers B or glass fibers can be embedded in the fiber composite material in any orientation and arrangement as a fabric F. However, they are not statistically uniformly distributed in the fiber composite material produced according to the invention, but in the form of a fabric, i.e. in planes with larger and smaller portions, i.e. in the form of substantially individual layers. The starting material is preferably a laminated or layered structure of the fiber composite material produced according to the invention.

[0077] Even in the production of fortifying fiber B, particularly glass fiber, adhesion promoter also can be applied as a part of sizing material.But, also can provide extra thermal debonding operation or destroy or remove another kind of debonding operation of the sizing material applied.Subsequently, then can apply the topcoat (finish) containing adhesion promoter on fortifying fiber or glass fiber, and this topcoat and corresponding matrix and required fiber-matrix adhesion match.Alternately, also can use polymer layer.In one embodiment, can use adhesion promoter and aminosilane adhesion promoter matched with matrix polymer, this matrix polymer contains crosslinkable polysulfur urethane and / or polyester urethane polymer as film former.

[0078] Preferred are finished reinforcement fibers or glass fibers, especially in the form of a woven fabric, with a modified silane sizing such as FK 800 topcoat; see R&G Glass Plain Fabric 25 g / m 2 FK 800 Glass Fabric R&G Twill 1901005 from R&G Faserverbundwerkstoffe GmbH, Waldenbuch 71111, Germany. This weave is very soft and will hardly fray when cut.

[0079] According to the present invention, the fabric F of reinforcing fibers B is in the form of a braid. The two-dimensional laminate obtainable from the braid of reinforcing fibers B in the manner of the present invention preferably contains a composite formed in the form of a layer by a layer of a two-dimensional reinforcing fiber layer B and a thermoplastic molding composition A, which is used as a matrix and wets and holds these two-dimensional reinforcing fiber layers B together. In a preferred embodiment, the matrix is ​​embedded in the reinforcing fibers / fiber layers B in the form of a layer, thereby forming a fiber composite material manufactured according to the present invention.

[0080] The braid used as fabric F according to the present invention is formed by weaving continuous fibers, in particular by weaving rovings. The weaving of (continuous) glass fibers is inevitably associated with the undulation of (reinforced) fibers. The undulation has a special effect of reducing the compressive strength parallel to the fiber. The characteristic of the undulation is that the (reinforced) fibers move up and down alternately relative to the plane of the fabric F, so they are not in an ideal parallel and stretched form. Considering the two-dimensional projection of the undulating fabric, the fibers are in an ideal stretched form in the warp and weft directions of the fabric. Ideal parallelism is essential for the optimal transmission of forces in the fibers. If the thermoplastic molding composition A used as the matrix M is embedded in the fabric F, the ideal parallelism of the (reinforced) fibers can be maintained. The deviation from the ideal parallelism is called fiber deformation and is measured by visual monitoring according to DIN EN ISO 13015, in particular by means of a suitable instrument or a camera-based system. The position of the fiber centerline is determined in the main direction relative to the length of the filament. A filament defines a bundle of fibers, which is also called roving, yarn, fiber bundle or filament bundle.

[0081] In a preferred embodiment, in the fiber composite material produced according to the present invention, the difference between the fiber centerline and the ideal linear (i.e., non-deformed) form based on the length of the fiber composite material or the shaped product T produced therefrom does not exceed 15%, preferably does not exceed 10%, and more preferably does not exceed 5%.

[0082] Preferably, the process according to the invention produces a fiber composite material having a proportion of reinforcing fibers B in the form of a fabric F in the range of 25% to 65% by volume as defined in DIN 1310, more preferably in the range of 30% to 55%.

[0083] Preferably, the process according to the invention produces a fiber composite material which has a proportion determined in accordance with ASTM D 2734-09 of not more than 5% by volume, wherein the remaining volume preferably consists entirely of the molding composition A.

[0084] Method step ii)

[0085] Process step ii) involves providing a thermoplastic molding composition A in the form of a matrix M which has at least 0.3 mol %, based on component A, of chemically reactive functional groups in the form of functional monomers.

[0086] Having chemically reactive functional groups, or being modified by chemically reactive functional groups, means that the (co)polymer contains monomers (as structural units) which generate reactive chemical groups in the (co)polymer.

[0087] Such chemically reactive functional groups react with chemical groups on the surface of reinforcing fibers B during the production of the fiber composite material produced according to the invention. Preferably, a thermoplastic molding composition A based on a (co)polymer used as a matrix is ​​used. Such a (co)polymer preferably comprises at least one functional monomer AI, the functionality of which reacts with chemical groups on the surface of reinforcing fibers B during the production of the fiber composite material. In the context of the present application, a (co)polymer comprising monomers AI is also referred to as polymer component (Aa).

[0088] Optionally, the thermoplastic molding composition A may additionally contain one or more (co)polymers, which optionally also do not contain such chemically reactive functional groups (and therefore do not contain functional monomers AI) and therefore do not react with chemical groups on the surface of the reinforcing fibers B during the production of the fiber composite material. In the context of the present application, such (co)polymers are also referred to as polymer components (Ab).

[0089] Preferably, the thermoplastic molding composition A for the matrix M is based on an amorphous or semi-crystalline polymer. More preferably, the thermoplastic molding composition A used as the matrix M is used in the form of a semi-crystalline polymer. A solid containing crystalline and amorphous regions (domains) is called a semi-crystalline. If the melt of the polymer is cooled, the chains of the polymer will move to an even smaller extent, and they will begin to arrange or crystallize regularly. But because they are entangled together, this process cannot occur in the entire melt and can only occur in the domain. In the residue of the melt, the chain will solidify in a disordered (amorphous) manner. The slower the melt is cooled, the greater the crystallinity of the polymer. Polymers with smaller side chains crystallize better than polymers with longer side chains. In contrast, crosslinked or branched polymers are unlikely to crystallize. According to DE 10 2011 084 519 A1, semicrystalline polyamides have a melting enthalpy of more than 25 J / g, measured in a second heating run according to the DSC method to ISO 11357 and integration of the melting peak, wherein this definition also applies to other semicrystalline polymers.

[0090] In method step ii), the amount of matrix M used is such that the fiber composite produced according to the invention is preferably based on 10 to 95 parts by mass, more preferably 20 to 50 parts by mass, even more preferably 23 to 40 parts by mass, and in particular 27 to 38 parts by mass of matrix M, based on 100 parts by mass of the fiber composite material.

[0091] The thermoplastic molding composition A provided as matrix M in process step ii) is preferably based on at least one polymer from the following group: polyolefins, polyamides, thermoplastic elastomers, polycarbonates, polybutadiene terephthalates, polylactides, polyphenylene sulfides and styrene copolymers.

[0092] Preferred styrene copolymers are styrene-acrylonitrile copolymers (SAN), α-methylstyrene-acrylonitrile copolymers (AMSAN), impact-modified styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymers (ABS), styrene-methyl methacrylate copolymers (SMMA), methacrylate-acrylonitrile-butadiene-styrene copolymers (MABS) or acrylate-styrene-acrylonitrile copolymers (ASA), wherein the styrene copolymer has been modified with a monomer (AI).

[0093] Blends of the abovementioned copolymers with polycarbonates or with semicrystalline polymers, in particular with polyamides, are also suitable, provided that the proportion of the semicrystalline mixture components in component A is less than 50% by weight.

[0094] Preferably according to the invention, at least one of the polymer components in the thermoplastic molding composition A has been modified with monomers AI (polymer component (Aa)). Any additional polymer components, preferably styrene copolymers, in particular as mentioned above, which have not been modified with monomers AI, may optionally be additionally present in the thermoplastic molding composition A (polymer component (Ab)).

[0095] Very particular preference is given to using SAN-(MI) copolymers (modified with monomers AI) as constituent of the thermoplastic molding composition A (optionally even as sole polymer constituent).

[0096] According to the invention, at least one of the (co)polymer components of the thermoplastic molding composition A is a (co)polymer having at least one chemically reactive functional group (polymer component (Aa)). Thus, in addition to the explicitly mentioned monomers, each of the copolymer components mentioned in the preceding paragraph in connection with process step ii) may also have reactive functionalities which can react with the surface of the reinforcing fibers B during the production of the fiber composite material. Thus, any of the above-mentioned (co)polymers may also constitute polymer component (Aa).

[0097] Thus, the above-mentioned polymer components, when used as polymer component (Aa), can usually also contain at least one monomer AI which imparts chemically reactive functional groups (and thus reacts with the reinforcing fibers B). In this case, these may preferably also be referred to as polystyrene (AI) copolymers, styrene acrylonitrile (AI) copolymers, α-methylstyrene-acrylonitrile (AI) copolymers, impact-modified acrylonitrile-styrene (AI) copolymers, acrylonitrile-butadiene-styrene (AI) copolymers (ABS-(AI)) and acrylonitrile-styrene-acrylate (AI) copolymers (ASA-(AI)). Blends of the above-mentioned copolymers with polycarbonates or polyamides are also possible.

[0098] Optionally, the above-mentioned polymer component, when it is used as polymer component (Aa), may further comprise a second monomer (or even a third monomer) having a chemically reactive functional group.

[0099] Thus, in particular, in the case of using maleic anhydride (MA) as monomer AI, the above polymer component (when it is used as polymer component (Aa)) can also be referred to as polystyrene-maleic anhydride copolymer, styrene-acrylonitrile-maleic anhydride copolymer, α-methylstyrene-acrylonitrile-maleic anhydride copolymer, impact-modified acrylonitrile-styrene-maleic anhydride copolymer, acrylonitrile-butadiene-styrene-maleic anhydride copolymer (ABS-MA) or acrylonitrile-styrene-acrylate-maleic anhydride copolymer (ASA-MA). It can also be a blend of the above copolymers with polycarbonate or polyamide. The same applies to other monomers AI.

[0100] In one embodiment, in process step ii), in addition to one or more polymer components (Aa), any one or more other (co)polymers (as polymer component (Ab)) which do not contain such functionality can also be used. Here, it is also preferred to use the above-mentioned (co)polymers polystyrene, styrene-acrylonitrile copolymers, α-methylstyrene-acrylonitrile copolymers, impact-modified acrylonitrile-styrene copolymers, acrylonitrile-butadiene-styrene copolymers (ABS) and acrylonitrile-styrene-acrylate copolymers (ASA), as well as blends of the mentioned (co)polymers with polycarbonates or polyamides, but in this case without functionality (and therefore without reactive monomers AI).

[0101] The thermoplastic molding composition A used is more preferably a polyolefin, even more preferably a polypropylene (PP) or a high-pressure polyethylene (HPPE). In this case, the thermoplastic molding composition A preferably contains more than 50% of polypropylene or copolymer (A-1). In one embodiment, this thermoplastic molding composition A contains at least 90% of copolymer A-1. In this case, the thermoplastic molding composition A can also consist solely of copolymer A-1.

[0102] Preferably, according to the invention, at least one of the components of the thermoplastic molding composition A contains a (co)polymer having at least one chemically reactive functional group as described herein and is referred to as polymer component (Aa). More preferably, at least one of the above polymer components is a polypropylene and / or at least one copolymer A-1 (styrene copolymers, in particular SAN, SMMA, ABS and ASA) containing at least one monomer AI.

[0103] In the particularly preferred case of using maleic anhydride (MA) as monomer AI, the polypropylene contains a polypropylene-maleic anhydride copolymer, and copolymer A-1 is particularly preferably a styrene-acrylonitrile-maleic anhydride copolymer (SAN-MA), a styrene-methyl methacrylate-maleic anhydride copolymer (SMMA-MA), an acrylonitrile-butadiene-styrene-maleic anhydride copolymer (ABS-MA) or an acrylate-styrene-acrylonitrile-maleic anhydride copolymer (ASA-MA).

[0104] In addition to at least one polymer component (Aa), any one or more other (co)polymers not containing such functionality may optionally be used as polymer component (Ab). This may preferably be polystyrene, SAN, SMMA, ABS and / or ASA (in each case without any monomer AI).

[0105] In an alternative embodiment, the thermoplastic molding composition A is preferably an amorphous molding composition, wherein the amorphous state of a thermoplastic molding composition (thermoplastic) means that the macromolecules are in a completely random arrangement without a regular arrangement or orientation, ie without equivalent separation.

[0106] Preferably, in this case, the entire thermoplastic molding composition A has amorphous thermoplastic properties and is therefore fusible and (largely) non-crystalline. As a result, the shrinkage of the thermoplastic molding composition A and therefore of the entire fiber composite material is relatively low. Particularly smooth surfaces can be achieved in the molded articles T produced from the fiber composite material produced according to the invention.

[0107] As a preferred amorphous molding composition, component A contains less than 50 parts by mass, more preferably less than 40 parts by mass of semi-crystalline content based on 100 parts by mass of component A. Semi-crystalline thermoplastics form both chemically regular regions and geometric regions, i.e., there are regions forming crystallites. Crystallites are parallel bundles of molecular segments or folds of molecular chains. Single chain molecules can partially pass through crystalline or amorphous regions. They can sometimes even belong to multiple crystallites at the same time.

[0108] The thermoplastic molding composition A may also be a blend of an amorphous thermoplastic polymer and a semicrystalline polymer.

[0109] The thermoplastic molding composition A is preferably a blend of a styrene copolymer AI, in particular SAN, with one or more polycarbonates and / or one or more semi-crystalline polymers, in particular polyamides, wherein the proportion of the semi-crystalline mixture components in component A is less than 50 parts by mass, preferably less than 40 parts by mass, relative to 100 parts by mass of the thermoplastic molding composition A.

[0110] Preferably, according to the invention, at least one thermoplastic molding composition A comprises at least one copolymer A-1, which comprises monomers AI that form covalent bonds with functional groups BI of embedded reinforcing fibers B. The proportion of monomers AI in the thermoplastic molding composition A can be selected in a variable manner. The higher the proportion of monomers AI and functional groups (BI), the stronger the bond between the thermoplastic molding composition A and the reinforcing fibers B can also be. Monomers AI can still be present as monomers in the copolymer A-1, or can be integrated into the copolymer A-1. Monomers AI are preferably integrated into the copolymer A-1.

[0111] In a preferred embodiment, copolymer A is formed from monomers AI in a proportion of at least 0.3 parts by mass, more preferably at least 0.5 parts by mass, even more preferably from 0.5 to 5 parts by mass, particularly preferably at least 1 part by mass, very particularly preferably from 1 to 5 parts by mass, based on 100 parts by mass of copolymer A.

[0112] The concentration of the functional groups (chemically reactive groups), based on 100 mol % of the monomers used to produce the thermoplastic molding composition A, is preferably at least 0.3 mol %, more preferably at least 0.5 mol %, even more preferably 1 mol %, particularly preferably 1 to 5 mol %.

[0113] In a preferred embodiment, the functional groups of the thermoplastic molding composition A are selected from the group consisting of anhydrides, esters, carboxyls, amides, imides, acrylates and glycidyl groups. Monomers AI that can form covalent bonds with the functional groups BI of the reinforcing fibers B include all monomers with this property. Preferred monomers AI here are monomers that can form covalent bonds by reacting with hydroxyl or amino groups.

[0114] Monomer AI preferably has:

[0115] (a) at least one functionality capable of forming a covalent bond with the functional groups BI on the surface of the reinforcing fibers B, preferably by reacting with hydroxyl and / or amino groups; and

[0116] (b) at least one second functionality capable of being incorporated into the copolymer A-1, preferably a double bond, more preferably a terminal double bond, which is preferably incorporated into the copolymer A-1 by free radical polymerization.

[0117] Optionally, the copolymer A-1 or the further (co)polymer present in the thermoplastic molding composition A may contain one or more further monomers capable of forming covalent or non-covalent bonds with the reinforcing fibers B.

[0118] In a preferred embodiment, monomer AI is selected from the group of maleic anhydride (MA), N-phenylmaleimide (PM), tert-butyl (meth)acrylate and glycidyl (meth)acrylate (GM). In a particularly preferred embodiment, monomer AI is selected from the group of maleic anhydride (MA), N-phenylmaleimide (PM), and glycidyl (meth)acrylate (GM). Two of these monomers AI may also be present in copolymer A-1.

[0119] The copolymers AI in the thermoplastic molding composition A may optionally include other functional monomers A-II. Preferred copolymers A-1 are styrene / maleic anhydride, styrene / acrylonitrile / maleic anhydride, styrene / glycidyl methacrylate, styrene / N-phenylmaleimide, styrene / acrylonitrile / N-phenylmaleimide, methyl methacrylate / N-phenylmaleimide, methyl methacrylate / maleic anhydride, methyl methacrylate / maleic anhydride / N-phenylmaleimide, acrylonitrile / styrene / tert-butyl (meth)acrylate, acrylonitrile / butadiene / styrene / tert-butyl (meth)acrylate and acrylonitrile / butyl acrylate / styrene / tert-butyl (meth)acrylate. Particularly preferred copolymers AI are styrene / maleic anhydride, styrene / acrylonitrile / maleic anhydride, styrene / glycidyl methacrylate, styrene / N-phenylmaleimide, styrene / acrylonitrile / N-phenylmaleimide, methyl methacrylate / N-phenylmaleimide and methyl methacrylate / maleic anhydride / N-phenylmaleimide.

[0120] The process according to the invention preferably provides a thermoplastic molding composition A consisting of polystyrene, in particular glass-transparent polystyrene "PS" or impact polystyrene or high-impact polystyrene "HIPS". The process according to the invention using glass-transparent polystyrene preferably produces (partially) translucent or transparent fiber composites.

[0121] In a particularly preferred embodiment, the polymer component (Aa) of the thermoplastic molding composition A used according to the invention is based on polypropylene. In this case, the polypropylene also comprises monomers AI which react with the surface of the reinforcing fibers B during production.

[0122] According to the invention, the feature "modified with chemically reactive functional groups" or "having chemically reactive functional groups" means in particular that maleic anhydride monomers are incorporated into the polymer chain of the (co)polymer used according to the invention.

[0123] Very particular preference is given to a process in which the chemically reactive functional groups of the thermoplastic molding composition A are based on components selected from the group of maleic anhydride, N-phenylmaleimide, tert-butyl (meth)acrylate and glycidyl (meth)acrylate, in particular from the group consisting of maleic anhydride, N-phenylmaleimide and glycidyl (meth)acrylate.

[0124] According to the present invention, the modified polypropylene particularly preferably used as the thermoplastic molding composition A is prepared from 90 to 99.7 parts by mass of unmodified polypropylene, preferably 95 to 99 parts by mass of unmodified polypropylene and 0.3 to 10 parts by mass, preferably 1 to 5 parts by mass of maleic anhydride, based on 100 parts by mass of the modified polypropylene. More preferably, the maleic anhydride content in component A is in the range of 0.1 to 6 parts by mass, even more preferably in the range of 1 to 5 parts by mass, in particular in the range of 3 to 4 parts by mass, based on 100 parts by mass of the modified polypropylene.

[0125] Mention should also be made of mixtures of styrene-acrylonitrile copolymers with α-methylstyrene-acrylonitrile copolymers. The acrylonitrile-butadiene-styrene copolymers preferably used according to the invention as thermoplastic molding compositions A are prepared by known methods from styrene, acrylonitrile, butadiene and functionalized further monomers AI, in particular methyl methacrylate.

[0126] Preferably, according to the invention, at least one of the (co)polymer components of the thermoplastic molding composition A is a (co)polymer having at least one of the chemically reactive functional groups described (polymer component (Aa)). This may also be a polymer component as described above, which contains at least one functional monomer AI in the molding composition mentioned. Optionally, any one or more other (co)polymers (as polymer component (Ab)) which do not contain such functionality may be used.

[0127] In a further preferred embodiment, the matrix M can consist of at least two different thermoplastic molding compositions A. These different types of molding compositions can preferably have different melt flow indices (MFI) and / or different comonomers or additives.

[0128] According to the present invention, the term "molecular weight" (Mw) in its broadest sense can be regarded as the mass of a molecule or the region of a molecule, in particular a polymer chain, a block polymer or a small molecule, which can be reported in g / mol (Da) and kg / mol (kDa). The molecular weight (Mw) is preferably the weight average molecular weight, which can be determined by methods known in the prior art.

[0129] The thermoplastic molding composition A used in step ii) of the process according to the invention preferably has a molecular weight Mw in the range of 10 000 to 800 000 g / mol, more preferably in the range of 20 000 to 600 000 g / mol, wherein the Mw can be determined by light scattering in tetrahydrofuran (GPC with UV detector). The molecular weight Mw of the thermoplastic molding composition A can vary within a range of + / - 20%. See: A. Müller, Polymer Charakterisierung [Polymer Characterization], Hanser Verlag 1996.

[0130] The thermoplastic molding composition A preferably contains a polypropylene modified by chemically reactive functional groups and, apart from the addition of monomers AI, is formed essentially from the same monomers as "conventional polypropylene", wherein the monomer content is + / - 5%, the molecular weight is + / - 20%, and the melt flow index measured at a temperature of 230° C. and a load of 2.16 kg according to ISO 1133 can vary by + / - 20%. Preferably, according to the invention, ISO 1133 refers to DIN EN ISO 1133-1:2012-03.

[0131] In a preferred embodiment, the melt volume flow rate (MVR) of the thermoplastic polymer composition A used as the polymer matrix, measured according to ISO 1133 at 230° C. / 2.16 kg, is between 0.1 and 400 cm 3 / 10min, more preferably in the range of 0.5 to 200cm 3 / 10min, particularly preferably in the range of 1 to 150cm 3 / 10min range.

[0132] In a particularly preferred embodiment, the thermoplastic polymer composition A used as the polymer matrix has a melt volume flow rate (MVR) of 50 to 200 cm / s measured at 230°C / 2.16 kg according to ISO 1133. 3 / 10min, more preferably 70 to 150cm 3 / 10min, particularly preferably in the range of 85 to 125cm 3 / 10min range.

[0133] According to the invention, the process is particularly preferred when the thermoplastic molding composition additionally contains 0.1 to 6 parts by mass of maleic anhydride, based on 100 parts by mass of polypropylene. Most preferably, the mass proportion of maleic anhydride is in the range of 0.2 to 5 parts by mass, particularly preferably in the range of 1 to 4 parts by mass, very particularly preferably in the range of 3 to 4 parts by mass, based on 100 parts by mass of polypropylene.

[0134] Method step iii)

[0135] Process step iii) involves optionally incorporating at least one additive C into the thermoplastic molding composition A serving as matrix M. The matrix M used according to the invention preferably contains 0.01 to 40 parts by mass of at least one additive C, more preferably 0.01 to 30 parts by mass, even more preferably 0.01 to 25 parts by mass, particularly preferably 1 to 20 parts by mass, per 100 parts by mass of the thermoplastic molding composition A, wherein the additive C is different from the base polymer and the reinforcing fibers B of the thermoplastic molding composition A.

[0136] The additives C used are preferably particulate mineral fillers, processing aids, stabilizers, oxidation retardants, thermal decomposition retardants, UV decomposition retardants, lubricants and mold release agents, flame retardants, dyes, pigments or plasticizers. According to the invention, it is also possible to preferably use two or more of these additives.

[0137] Preferred particulate mineral fillers are selected from the group consisting of amorphous silicon dioxide, carbonates, in particular magnesium carbonate, calcium carbonate (chalk), powdered quartz, mica, silicates, in particular clay, muscovite, biotite, suzoite, tinmaletite, talc, chlorite, phlogopite, feldspar and calcium silicates, in particular wollastonite or kaolin. Kaolin is a very particularly preferred mineral filler.

[0138] Preferred UV stabilizers are selected from the group of substituted resorcinols, salicylates, benzotriazoles and benzophenones.

[0139] Preferred oxidation retarders, also called heat stabilizers, are selected from the group consisting of sterically hindered phenols, hydroquinones, secondary aromatic amines, optionally in combination with phosphoric acid or their salts, and mixtures of these compositions.

[0140] Preferred lubricants and mold release agents are selected from the group consisting of stearic acid, stearyl alcohol, alkyl stearates, stearamide, in particular and esters of pentaerythritol and long-chain fatty acids. Calcium, zinc or aluminum salts of stearic acid can be used, as well as dialkyl ketones, particularly distearyl ketone. In addition, ethylene oxide-propylene oxide copolymers can also be used as lubricants and release agents. In addition, natural waxes and synthetic waxes can be used. These include polypropylene wax, polyethylene wax, polyamide wax, grafted polyolefin wax, HDPE wax, PTFE wax, EBS wax, montan wax, carnauba wax and beeswax.

[0141] The flame retardant can be a halogenated compound or a halogen-free compound. Suitable halogen compounds (wherein brominated compounds are preferred over chlorinated compounds) remain stable in the production and processing of the molding compound of the present invention, so that corrosive gases are not released and the efficacy is not impaired. However, it is preferred to use halogen-free compounds, more preferably phosphorus compounds, particularly phosphine oxides and phosphoric acid derivatives and salts of phosphoric acid and phosphoric acid derivatives as flame retardants. More preferably, the phosphorus compound contains esters, alkyls, cycloalkyls and / or aryls. Also suitable are oligomeric phosphorus compounds having a molecular weight of less than 2000 g / mol, such as described in EP-A 0363 608.

[0142] Pigments and dyes used as additives are common knowledge; see, e.g., R. and H. Müller, Taschenbuch der Kunststoffadditive [Handbook of Plastics Additives], Carl Hanser Verlag, 1983, p. 494 to 510. Preferred pigments are white pigments from the group of zinc oxide, zinc sulfide, white lead, lithopone, antimony white and titanium dioxide. Of the two most common crystal modifications of titanium dioxide (rutile and anatase), rutile is particularly useful for whitening the thermoplastic molding compositions used according to the invention.

[0143] Black pigments which can likewise be used as additives according to the invention are iron oxide black (Fe3O4), spinel black (Cu(Cr,Fe)2O4), manganese black (equivalent to a mixture of manganese dioxide, silicon oxide and iron oxide), cobalt black and antimony black, and more preferably carbon black, which is usually used in the form of furnace black or gas black (in this respect, see G. Benzing, Pigmente für Anstrichmittel [Pigments for Paints], Expert-Verlag (1988), p. 78ff). Of course, according to the invention, inorganic color pigments such as chromium oxide green or organic color pigments, in particular azo pigments and phthalocyanines, can be used to establish specific shades. Such pigments are generally commercially available. In addition, it can be advantageous to use the pigments or dyes mentioned in mixtures, in particular carbon blacks containing copper phthalocyanine, which generally contribute to the color dispersion in thermoplastics.

[0144] Preferably, at least one additive C is incorporated into the thermoplastic molding composition A by mixing. The mixing is preferably carried out in an extruder, in particular in a co-rotating twin-screw extruder, a counter-rotating twin-screw extruder, a planetary roller extruder or a co-kneader. Mixing includes the process operations of conveying, melting, dispersing, degassing, pressure accumulation and extrusion (punching out).

[0145] Method steps iv) to vi)

[0146] After the at least one additive C has been optionally incorporated into the thermoplastic molding composition A serving as matrix M, it is introduced into the at least one fabric F provided in process step iv).

[0147] In process step v), the chemically reactive functional groups of the thermoplastic molding composition A react with polar groups on the surface of the reinforcing fibers B treated with the silane size before the fiber composite material is cooled in process step vi), and this is optionally followed by further process steps.

[0148] The process according to the invention, in particular process steps iv) and v) or optional process step vi), is preferably carried out on a double-belt press, a batch-heated press or a static press. In particular, a double-belt press is capable of producing fiber composites in a quasi-continuous manner from a powder-based or film-based thermoplastic molding composition by conversion into a melt.

[0149] The thermoplastic molding composition A serving as matrix M is introduced into at least one fabric F by embedding the thermoplastic molding composition A in the reinforcing fibers B by means of a relative movement in which the reinforcing fibers B remain stationary except for a one-dimensional production feed, and subsequently consolidating a composite consisting of at least one fabric F and matrix M.

[0150] The relative movement of the thermoplastic molding composition A with respect to the reinforcing fibers B displaces the air present between the reinforcing fibers F. As a result, air inclusions in the fiber composite material are reduced and good bonding between the thermoplastic molding composition A and the reinforcing fibers B is prevented, especially when the molding composition A is embedded in the form of a layer. According to the invention, preferably a (mostly) pore-free material composite is obtained after impregnation and consolidation.

[0151] Thermoplastic molding composition A is realized by fixing fortifying fiber B in the relative moving direction with respect to the relative movement of fortifying fiber B. Produce this fixing because in the case of amorphous thermoplastics by at least 10 ℃ temperature higher than crystallite melting temperature or glass transition temperature, by> 10 bar surface pressure produces the upstream and downstream of the moving zone of thermoplastic molding composition A, fixing fortifying fiber B is realized by mechanical clamping, winding or by fastening element, and this control is by applying opposite force to keep under constant strain.In this way, fortifying fiber B is fixed in place so that the strain of longitudinal direction prevents movement in any spatial direction.If fixing fortifying fiber in this way, and make thermoplastic molding composition bear at least 1 second under the above-mentioned pressure and temperature, then thermoplastic molding composition can move in the gap between fortifying fiber.In case thermoplastic molding composition completes its movement, fortifying fiber is just removed from temperature and pressure zone.

[0152] Here, the reinforcing fibers remain motionless except for continuous or discontinuous one-dimensional production feed. Preferably, according to the present invention, the reinforcing fibers B in the form of a braid are fixed and kept under tension by an automatic drawing system in the form of a roller formed on a delayed unwinding drum upstream of the zone where temperature and pressure are applied, and as a consolidated stack downstream of the zone where temperature and pressure are applied.

[0153] In addition to the one-dimensional production feed, consolidation with process step iv) is essential to the process of the invention. Consolidation in a broader sense is a bonding process in which physical processes lead to the development of strength at the junction of the matrix M and the at least one fabric F. In principle, there are four main mechanisms in the consolidation process: (if appropriate) fiber impregnation, laminate consolidation, molecular penetration and curing.

[0154] When pre-impregnated semi-finished fiber products (called prepregs or "pre-impregnated fibers") and undried semi-finished fiber products are used as fabric F, the impregnation of the reinforcing fibers B used in the fabric F according to the invention is not carried out during the consolidation process. Usually, no distinction is made in the literature between the terms "consolidation" and "impregnation", because laminate consolidation and molecular penetration only account for a small part of the total consolidation time. In the entire process, this proportion of laminate consolidation and molecular penetration is usually quantified in the order of magnitude of about 1%. Therefore, the consolidation process can also optionally be directly referred to as an impregnation process. Therefore, in particular by using already pre-impregnated semi-finished products or fabrics, short cycle times in the processing can be achieved.

[0155] During the processing of the laminate, in consolidation, the surface of the thermoplastic molding composition as the matrix polymer and the reinforcing fibers B of the fabric F are connected to each other at high consolidation pressures and high temperatures until completely intimate contact is formed. Problematic air inclusions may occur here. Only by exposure to consolidation pressure and / or optional decompression can the inclusion of air or other gases be minimized. The intimate contact formed during the consolidation of the laminate means that, ideally, the surface roughness of the connection partners (here the matrix polymer and the fabric) is uniform so that the contact can also be over the entire surface area. Good contact between the connection partners is important because a mechanically durable bond can only be formed in the contact area. Although completely intimate contact can also be achieved at low consolidation pressures, this will prolong the processing time.

[0156] Only then does the molecular penetration of the fabric F begin in the areas where the matrix polymer and the fabric F have already come into close contact. Due to the thermal activation of the molecules in the matrix and the associated increased mobility, in the molecular penetration the polymer chains diffuse into adjacent layers, so that the chain ends of the polymers of the thermoplastic molding composition used as matrix can form new entanglements and loops with polymer chains in adjacent layers.

[0157] The molecular permeation resulting from the diffusion of polymer chains and the resulting self-adhesion is not only time-dependent; it often requires flow effects as a driving force, in particular microscale flow motions due to the applied consolidation pressure. After the molecular permeation is complete, the laminate is cooled in the last step and thus becomes dimensionally stable (cured). Then, due to the cooling, the final pore volume, which was minimized by the application of the consolidation pressure, remains essentially unchanged at the end of the consolidation stage.

[0158] However, process-related, heat-induced internal stresses and deformations can also remain unchanged in the fiber composite material. It is also important that amorphous thermoplastics retain their molecular orientation last assumed during the diffusion process when cooling, while semi-crystalline thermoplastics recrystallize from the molten state during the cooling process. In different cases, the cooling rate also determines the degree of crystallinity and the formation of spherulites in method step iv). The degree of crystallinity is the proportion of the thermoplastic molecular structure in crystalline form. The mechanical and chemical properties (solvent stability, etc.) of the partially crystalline thermoplastic composition ultimately depend on this. Therefore, the consolidation of the thermoplastic material used as matrix M according to the invention is a highly nonlinear process, because it includes the different physical processes mentioned, which occur simultaneously to a certain extent. These processes have a significant influence on the final composite quality and therefore also on the fiber composite material produced according to the invention.

[0159] Insufficient consolidation can therefore lead to chain reactions such as trapped porosity, internal stresses, deformations, in particular distortions, and in some cases premature mechanical failure of the fiber composite material. A meaningful model for the process carried out here is therefore essential in order to be able to accurately predict the consolidation situation. Such a process model gives the input-output relationship between the process parameters and the quality of the molded article T made of the fiber composite material produced according to the invention, which can reduce the expensive "trial-and-error" optimization of the technical equipment used according to the invention. Therefore, the reliable predictions obtained from the simulation about the quality of the molded article T provide an effective way to optimize method step iv) or method steps (iv) to (vi). It can therefore be determined whether the consolidation quality meets the criteria applied to the manufactured molded article F. Therefore, a complete simulation of the consolidation process takes into account laminate consolidation, pore compaction, geometric deformation, molecular penetration, thermal degradation, crystallization as well as internal stresses and distortions. Mathematical models cannot completely replace physical experiments, but they are combined to allow simple parameter studies that provide basic information about the process that is otherwise difficult to measure directly or, if it can be measured, in a time-consuming manner.

[0160] Process steps iv) and v), in particular consolidation, are carried out at a temperature of at least 200°C, preferably at an elevated temperature of at least 250°C, and more preferably at a temperature of at least 300°C.

[0161] Process steps iv) and v), in particular consolidation, are carried out in a pressure range of 1 to 1000 bar, preferably in a pressure range of 5 to 500 bar, more preferably in a pressure range of 10 to 50 bar.

[0162] Process steps iv) and v) are preferably carried out with a residence time of from 1 to 60 seconds.

[0163] The process according to the invention is preferably carried out during process steps ii) to v) at a temperature of at least 200° C. for a residence time of not more than 10 minutes, preferably not more than 5 minutes, more preferably not more than 2 minutes and particularly preferably not more than 1 minute. For higher temperatures, correspondingly shorter residence times are applicable, which the person skilled in the art must select depending on the thermoplastic used in each case.

[0164] The polar groups on the surface of the reinforcing fibers B treated with the silane size are important for the reaction of the chemically reactive functional groups of the thermoplastic molding composition A in the matrix M with the reinforcing fibers B cured in process step v).

[0165] For this purpose, the size applied to the reinforcing fibers is an impregnation liquid, which is applied to the reinforcing fibers B by spraying or dipping, in particular before further processing, to obtain the braid used according to the invention. The sized fibers are softer and more stable to mechanical stresses. Without sizing, the warp yarns can easily become brittle and eventually break due to continuous friction with the weft yarns.

[0166] In the production of glass fibers, these fibers are preferably drawn from the melt at high speed. The thickness of the fibers is determined here by the size of the nozzle and the drawing rate. The hot fibers are cooled by water sprays and moistened with the size by means of an impregnating roller, and the individual filaments are then immediately bundled into rovings. The size has several functions. The rovings are bonded by the size binder and thus have sufficient stability, which prevents wear during transportation and the unraveling or breaking of the individual fibers in the roving. Since the size usually contains less water, the rovings must be dried. For this purpose, they are wound into "cakes" while wet and then dried, or they are processed while wet and then dried. The glass fibers thus obtained can then be incorporated into thermoplastics for reinforcement. Typically, the weight proportion of size in the dry glass fibers is in the range of 0.1% to 10% by weight.

[0167] Method step vi)

[0168] In method step vi), the fiber composite material is cooled and, optionally, further method steps follow.

[0169] A further method step is preferably the production of a moulded article T. In a preferred embodiment, the process then comprises three-dimensional shaping of the moulded article T as a further method step.

[0170] The three-dimensional shaping can be achieved in the desired manner, for example by mechanical shaping of a shaped body, which can also be an embossed drum. Preferably, the cooled fiber composite material obtained by method step vi) is completed in a further method step, in particular by conventional cutting methods, preferably shear cutting, water jet cutting, laser cutting or ultrasonic cutting, and then heated to a certain temperature, so that the fiber composite material becomes shapeable and the thermoplastic molding composition A is in (partially) molten form and can be shaped in a shaped body, in particular in a two-stage steel mold. Alternatively or additionally, cold forming of the solidified fiber composite material is also possible.

[0171] Preferably, at the end of the process, after method step vi), a (mostly) solid fiber composite sheet is obtained.

[0172] Further process steps or even cooling under elevated pressure can be carried out at a later joining point or elsewhere. Optionally, the molded article T can be further processed, in particular deburred, polished or colored.

[0173] The process according to the invention comprising process steps i) to vi) can be carried out continuously, semi-continuously or batchwise. In a preferred embodiment, the process is carried out as a continuous process, in particular as a continuous process for producing smooth or three-dimensional fiber composite sheets.

[0174] Alternatively, the molded articles T can also be produced in a semi-continuous or discontinuous manner. In the case of fiber composites based on an amorphous thermoplastic matrix M, these materials can be equipped with fins during the injection molding process or laminated (welded) as an outer layer to a foamed thermoplastic core or a honeycomb core. The increase in component stiffness due to the fins (formation of the fin structure) can be explained by the increase in the area moment of inertia. In general, the optimal fin size includes production-related, aesthetic and design considerations.

[0175] In a particularly preferred embodiment, the present invention relates to a process according to the invention for producing a thermoplastic fiber composite material, wherein component A is produced from 90% to 99.7% polypropylene and 0.1% to 10% maleic anhydride, wherein the fabric F is a woven fabric and the residence time required for producing the fiber composite material at a temperature of at least 150° C. does not exceed 10 minutes.

[0176] The present invention preferably provides a method for producing a fiber composite material, the fiber composite material comprising a thermoplastic molding composition A (as a polymer matrix M), reinforcing fibers B, the method comprising the following steps:

[0177] i) providing at least one fabric F in the form of a woven fabric consisting of reinforcing fibers B treated with a silane size,

[0178] ii) providing a thermoplastic molding composition A serving as matrix M, which, based on component A, has at least 0.3 mol % of chemically reactive functional groups in the form of functional monomers,

[0179] iii) optionally incorporating at least one additive C into the thermoplastic molding composition A,

[0180] iv) introducing the thermoplastic molding composition A serving as matrix M into at least one fabric F by embedding the thermoplastic molding composition A in the reinforcing fibers B by means of a relative movement in which the reinforcing fibers B remain stationary except for a continuous or discontinuous one-dimensional production feed, and consolidating the composite material consisting of the at least one fabric F and the matrix M,

[0181] v) reacting the chemically reactive functional groups of the thermoplastic molding composition A with the polar groups at the surface of the reinforcing fibers B which have been treated with the silane size,

[0182] vi) cooling the fiber composite material, and optionally further method steps,

[0183] wherein the chemically reactive functional groups of the thermoplastic molding composition A are based on maleic anhydride, and steps iv) to vi) are carried out at a temperature of at least 150° C., and steps v) to vi) are carried out by pressing under elevated pressure, and the thermoplastic molding composition contains 90 to 99.7% by weight of polypropylene and 0.1 to 10% by weight of maleic anhydride, and 0 to 40% by weight, preferably 0.1 to 25% by weight, of at least one additive C.

[0184] For 10 to 95% by weight of the thermoplastic molding composition A, preference is given to using 5 to 90% of a fabric F composed of reinforcing fibers B.

[0185] In other embodiments, other groups of reinforcing fibers B are joined to the matrix M via other different fiber-matrix adhesions. If three or more groups of reinforcing fibers B with different fiber-matrix adhesions are used, the behavior of the fiber composite material can be further influenced in a controlled and highly personalized manner and adjusted to the respective use of the fiber composite material. Here, different fiber types or the same fiber types can be used in each case.

[0186] Warp and weft can be made of different reinforcing fiber compositions and / or thicknesses equally.In addition, warp and weft may have been processed with different sizing materials or sizing materials of different concentrations.

[0187] Each group of reinforcing fibers B can be treated with different adhesion promoter compositions to produce different fiber-matrix adhesions. The different compositions can differ only in concentration, or have other compositions. Importantly, the different adhesion promoter compositions establish significantly different fiber-matrix adhesions.

[0188] The invention is described in detail in the following examples, figures and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0189] Figure 1 A fibrous composite material (1) obtained by the method of the invention is shown. The length of the fibrous composite material (1) is the extension in direction (2), wherein (2) is at the same time the main direction of the continuous fibers used in the fabric F. (3a) and (3b) are examples of the progression of the continuous fibers moving in the window (4). The fibrous composite material (1) obtainable by the method of the invention is characterized in that the height of the window (4) does not exceed 15%, more preferably does not exceed 5%, of the length (2) of the fibrous composite material (1).

[0190] Figure 2 A fabric F is shown with typical fiber twisting due to relative movement of the fibers.

[0191] Figure 3 A fiber composite material obtainable according to the invention is shown in which relative movement of the reinforcing fibers B of a fabric F is prevented by embedding a thermoplastic molding composition in the reinforcing fibers and consolidating the composite by means of a relative movement in which the reinforcing fibers B remain stationary except for a one-dimensional production feed. DETAILED DESCRIPTION

[0192] Example

[0193] The process of the invention can be carried out on a double-belt press, a batch press or a static press which is capable of producing fiber / film composites quasi-continuously from polymer films, melts or powders.

[0194] Producible laminate thickness: 0.1 to 15.0 mm

[0195] Output: 0.1-1000m / h, depending on quality and component thickness

[0196] Mould pressure: Press unit 2 up to 60 bar, infinitely adjustable minimum and maximum mould dimensions (optional)

[0197] Mold temperature control: at least one heating zone and at least one cooling zone

[0198] Mold temperature: up to 500°C

[0199] The flexural strength is determined by a three-point bending test or a four-point bending test according to DIN 14125:2011-05.

[0200] See: https: / / de.wikipedia.org / wiki / Biegefestigkeit

[0201] Components:

[0202] A1: Melt volume flow rate (MVR) 100 cm at 230°C / 2.16 kg 3 / 10min of polypropylene (measured according to ISO1133)

[0203] A2: Maleic anhydride (MA)

[0204] A3: A mixture of A1 and A2, functional group concentration: 3% MA

[0205] B1: 2 / 2 glass fiber twill weave, basis weight = about 600g / m 2 , weft + warp = 1200 tex [e.g. GW123-580K2 from PD Glasseiden GmbH]

[0206] About the bending strength obtained, compare the combination of A1 and B1 and A3 and B1 in Table 1. Both combinations are produced under the same processing parameters (pressure, time and temperature). Bending rigidity is a feature for evaluating the quality of fiber-matrix adhesion and the quality of mechanical components. In the case of combination A1+B1 and A3a+B1a, the sheet tested is produced on a static press, and the reinforcing fibers are processed (represented by "a") according to the prior art and therefore in a non-deformation-free mode. The A3b+B1b combination is produced by a production technology, which, according to method step iv) of the method claimed here, ensures the deformation-free state of the reinforcing fibers (represented by "b").

[0207] Table 1

[0208] combination Flexural strength (normalized) A1+B1 100% A3a+B1a 111% A3b+B1b 126%

[0209] It was found that the process according to the invention makes it possible to obtain a fiber composite (material) which, in terms of its flexural strength, is 26% higher than a fiber composite (material) based on the same matrix and the same reinforcing fibers, but which is not produced by process step iv) but by the process in EP 3 286 258 B1.

[0210] Optional further processing

[0211] Experiments also show that the fiber composite material obtained by the method of the present invention has good formability for three-dimensional semi-finished products, such as half-shell-shaped semi-finished products. In addition, it is also found that the fiber composite material obtained is printable and laminated.

[0212] Summary of experimental results

[0213] Evaluations in the context of the present invention have shown that fiber composites, i.e. organic sheets and semi-finished products produced therefrom, with increased bending strength can be produced reproducibly by method step iv). The fiber composites / fiber composites according to the invention can be produced in colorless or colored form. The fiber composites / fiber composites also exhibit good to very good optical, tactile and mechanical properties, in particular with regard to their bending strength. The fiber distortion that usually occurs in the fabric F can be successfully prevented by the production method according to the invention, so that the fiber composite (material) has only slight fiber distortion. The fiber composites / fiber composites obtainable according to the invention can be produced in a semi-automatic or fully automatic manner by a continuous process. The fiber composites / fiber composites (organic sheets) obtainable according to the invention have good formability for three-dimensional semi-finished products.

Claims

1. A method for producing a fiber composite material, the fiber composite material comprising a thermoplastic molding composition A as a polymer matrix M, and reinforcing fibers B, the method comprising the following steps: i) providing at least one fabric F in the form of a woven fabric, said fabric F consisting of reinforcing fibers B treated with a silane size, ii) providing a thermoplastic molding composition A serving as matrix M, said thermoplastic molding composition A having at least 0.3 mol % of chemically reactive functional groups in the form of functional monomers, based on component A, iii) optionally incorporating at least one additive C into the thermoplastic molding composition A, iv) introducing the thermoplastic molding composition A serving as matrix M into the at least one fabric F by embedding the thermoplastic molding composition A in the reinforcing fibers B by means of a relative movement in which the reinforcing fibers B remain stationary except for a continuous or discontinuous one-dimensional production feed, and consolidating this composite consisting of the at least one fabric F and the matrix M, v) reacting the chemically reactive functional groups of the thermoplastic molding composition A with the polar groups at the surface of the reinforcing fibers B treated with the silane size, vi) cooling the fiber composite material, and optionally further method steps, wherein the chemically reactive functional groups of the thermoplastic molding composition A are based on components selected from the group consisting of maleic anhydride, N-phenylmaleimide and glycidyl (meth)acrylate, and steps iv) to vi) are carried out at a temperature of at least 150° C., and step v) to vi) are carried out by pressing under elevated pressure.

2. The method for producing a thermoplastic fiber composite material according to claim 1, characterized in that The thermoplastic molding compositions A are based on amorphous or semicrystalline plastics.

3. The method for producing a thermoplastic fiber composite material according to claim 2, characterized in that The thermoplastic molding composition A is based on at least one polymer from the following group: polyolefins, polyamides, thermoplastic elastomers, polycarbonates, polybutadiene terephthalates, polylactides, polyphenylene sulfides and styrene copolymers.

4. The method for producing a thermoplastic fiber composite material according to claim 3, characterized in that The polyolefin used was polypropylene.

5. Method for producing a thermoplastic fiber composite material according to one or more of claims 1 to 4, characterized in that Reinforcement fibers B treated with silane size were used.

6. The method for producing a thermoplastic fiber composite material according to claim 5, characterized in that The reinforcing fibers B used were glass fibers.

7. The method for producing a thermoplastic fiber composite material according to claim 6, characterized in that The glass fiber used as the reinforcing fiber B has a silanol group as a chemically reactive functional group on the surface.

8. Method for producing a thermoplastic fiber composite material according to one or more of claims 1 to 7, characterized in that The process, in particular process steps iv) and v) or optionally also process step vi), is carried out on a double-belt press, a batch-heated press or a static press.

9. Method for producing a thermoplastic fiber composite material according to one or more of claims 1 to 8, characterized in that The temperature in producing the fiber composite material is at least 150°C, preferably at least 200°C, and more preferably at least 250°C.

10. Method for producing a thermoplastic fiber composite material according to one or more of claims 1 to 9, characterized in that The residence time in the production of the fiber composite material at a temperature of at least 200° C. is not more than 10 minutes, preferably not more than 5 minutes, more preferably not more than 2 minutes and in particular not more than 1 minute.

11. Method for producing a thermoplastic fiber composite material according to one or more of claims 1 to 10, characterized in that The relative movement of the thermoplastic molding composition A with respect to the reinforcing fibers B is achieved by fixing the reinforcing fibers B in the relative movement direction.

12. The method for producing a thermoplastic fiber composite material according to claim 11, characterized in that Upstream and downstream of the zone in which the movement of the thermoplastic molding composition A is produced by a surface pressure of >10 bar at a temperature of at least 10°C above the crystallite melting temperature or glass transition temperature in the case of amorphous thermoplastics, the fixing of the reinforcing fibers B is achieved by mechanical clamping, winding or with the aid of fastening elements and this control is maintained by applying opposing forces under constant strain.

13. The method for producing a thermoplastic fiber composite material according to claim 11 or 12, characterized in that The reinforcing fibers B are fixed in place so that strain in the longitudinal direction prevents movement in any spatial direction.

14. Method for producing a thermoplastic fiber composite material according to one or more of claims 1 to 13, characterized in that The reinforcing fibers B in the form of a braid are fixed and kept under tension by an automatic drawing system in the form of rollers on delayed unwinding drums upstream of the zone of application of temperature and pressure, and as a consolidated stack downstream of said zone of application of temperature and pressure.

15. Method for producing a thermoplastic fiber composite material according to one or more of claims 1 to 14, characterized in that The chemically reactive functional groups of the thermoplastic molding composition A are based on maleic anhydride, and steps iv) to vi) are carried out at a temperature of at least 150° C. and steps v) to vi) are carried out by pressing under elevated pressure, and the thermoplastic molding composition contains 90 to 99.7% by weight of polypropylene and 0.1 to 10% by weight of maleic anhydride and 0 to 40% by weight, preferably 0.1 to 25% by weight, of at least one additive C.